Nature based solution to climate change: Ecosystem based adaptation: How effective for climate change strategies? - Oktaviani, Aliyah; Masjud, Yunita Ismail (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Climate change is produced by a shift in the planet's energy balance, which determines how much of the energy from the sun that enters the earth (and its atmosphere) is released back into space. The planet gains energy when we lower the quantity of solar radiation reflected into space, just as individuals gain weight when there is an imbalance between calories in and calories out [1]. Climate change is an important thing that we must note, the climate may change but in the change there are things that we must consider, namely about the impact of climate change, this is related to SDG 13 which seeks to combat climate change and overcome its impacts. The SDG 13.1 target specifically aims to strengthen resilience and adaptive capacity to climate-related hazards and natural disasters. Such events represent the cutting edge of climate change. The frequency and intensity increase. There are many ways to mitigate and adapt to climate change some that we can do by apply of Nature Based Solution to Climate change and Ecosystem based adaptation that can be expected to play an effective role in climate change mitigation strategies. In addition, there are several things that must be considered in terms of social, environmental and also economic so that what we apply in handling climate change can be optimal and work well, the object in this discussion is about Nature Based Solution and Ecosystem Based Adaptation how effective it is to overcome climate change problems by using several methods such are measurements, vulnerability, a case, tools, several data and evidence that ultimately in this discussion proved that both are very helpful and effective in adaptation and mitigation to climate change. Nature based solution and ecosystem based adaptation are both things that cannot be separated because both are one part that has the same function in one way of handling climate change.